Prophylactic efficiency of the administration of vitamin, mineral and sorbent complexes on bone tissue in female rats against the background of chronic alcohol consumption - O. A. Makarenko; V. V. Kika; I. V. Khodakov; L. M. Khromagina (Regulatory Mechanisms in Biosystems, 2023)
Among the general effects of alcohol use, it has a negative effect on the bone system, so the development of prevention methods is becoming an increasingly urgent problem. The present study was aimed at evaluating the efficiency of the preventive complexes for the bone system in chronic alcohol intoxication. The study was conducted on 2-month-old female rats for 104 days. Chronic alcoholism in animals was simulated by replacing drinking water with an ethanol solution, the concentration of which was gradually increased from 8–25%. The prophylactic was administered by introducing into the diet a complex of vitamins (P, C, D) and minerals (Cu, Mg, Zn, Se, Mn), the main component of which was crushed oyster shells processed with citric acid. The second prophylactic complex was the clay mineral montmorillonite in combination with vitamins P, C, D. The biochemical markers of resorption (elastase and acid phosphatase activity), osteogenesis (calcium content, alkaline phosphatase activity) and the state of the antioxidant system (catalase, superoxide dismutase, glutathione reductase activity, malondialdehyde content) were determined in bones (jaws and femurs). Chronic alcohol consumption led to an increase in the degree of atrophy of the alveolar process, a decrease in femur bone density due to a decrease in the mineral component in bone tissue, and did not affect the state of the lumbar vertebrae. Chronic alcohol intoxication led to a decrease in the level of calcium in the blood serum of rats, and to a decrease in the alkaline phosphatase activity and the calcium content in the bone tissue of the jaws and femur against the background of increases in the activities of acid phosphatase and elastase. A significant decrease in the activity of the main antioxidant enzymes (superoxide dismutase, catalase and glutathione reductase) in bone tissue of animals against the background of an increase in the malondialdehyde content under conditions of chronic alcoholization has been established. The use of the complex with crushed oyster shells effectively prevented atrophy ofthe alveolar process in the jaws, did not affect the morphometric parameters in the femur and vertebrae, but normalized the activities of serum alkaline phosphatase and catalase, bone elastase, acid phosphatase, superoxide dismutase and glutathione reductase against the background of restoring the levels of calcium and malondialdehyde both in the serum and in the bone tissue of rats subjected to chronic alcoholization. Prophylactic administration of the vitamin complex with montmorillonite had a much weaker effect on the studied indicators. The obtained research results allow us to conclude that the osteoprotective and antioxidant efficiency of the complex with crushed oyster shells is more pronounced than that of montmorillonite under conditions of chronic alcohol intoxication.